DETERMINAN KESEJAHTERAAN PENDUDUK LANJUT USIA DI DESA KEMENUH GIANYAR - Anggreni, Ni Luh Putu Evi; Ayuningsasi, Anak Agung Ketut (Buletin Studi Ekonomi, 2023)
This study aims to analyze the effect of marital status, employment status, and social support simultaneously and partially on the welfare of the elderly population in Kemenuh Village, Sukawati District, Gianyar Regency. This study uses a quantitative approach in the form of associative. Sampling was carried out by nonprobability sampling, namely the accidental sampling method. The elderly population in Kemenuh Village is 1,499 people and a sample of 120 people is taken. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that marital status, employment status, and social support simultaneously have a significant effect on the welfare of the elderly population in Kemenuh Village. Marital status, employment status, and social support partially have a positive and significant effect on the welfare of the elderly population in Kemenuh Village, Sukawati District, Gianyar Regency. The results of this study can contribute to the development of welfare theory, especially concerning the welfare of the elderly population which is starting to receive attention.